Ambient Temperature Is Correlated With the Severity of Neonatal Hypoxic-Ischemic Brain Injury via Microglial Accumulation in Mice - Zen, Rika; Terashima, Tomoya; Tsuji, Shunichiro; Katagi, Miwako; Ohashi, Natsuko; Nobuta, Yuri; Higuchi, Asuka; Kanai, Hirohiko; Murakami, Takashi; Kojima, Hideto (Frontiers in Pediatrics, 2022)
Background: The pathophysiology of neonatal hypoxic-ischemic encephalopathy (HIE) has been studied in several rodent models to develop novel treatments. Although it is well known that high ambient temperature results in severe HIE, the effect of subtle changes in ambient temperature during a hypoxic-ischemic (HI) insult has not been studied. Therefore, in order to clarify the difference of pathophysiological change among the HIE models due to the influence of small changes in chamber temperature, three-step gradual change of 0.5 °C each were prepared in ambient temperature during hypoxic exposure. Methods: Blood flow in the left common carotid artery (CCA) of neonatal mice was interrupted using bipolar electronic forceps under general and local anesthesia. The mice were subsequently subjected to 10% hypoxic exposure for 50 min at 36.0 °C, 36.5 °C, or 37.0 °C. A control group was also included in the study. The size of the striatum and hippocampus and the volume reduction rate of the hemisphere in the section containing them on the ischemic side were evaluated using microtubule associated protein 2 (MAP2) immunostaining. The accumulation of Iba1-positive cells was investigated to assess inflammation. Additionally, rotarod and open-field tests were performed 2 weeks after HI insult to assess its effect on physiological conditions. Results: MAP2 staining revealed that the higher the temperature during hypoxia, the more severe the volume reduction rate in the hemisphere, striatum, and hippocampus. The number of Iba1-positive cells in the ipsilateral lesion gradually increased with increasing temperature, and there was a significant difference in motor function in the 36.5 °C and 37.0 °C groups compared with the sham group. In the rotarod and open-field tests, there was a significant decrease in performance in the 36.5 °C or 37.0 °C groups compared with the 36.0 °C and sham groups. Conclusions: Even a small gradual change of 0.5 °C produced a significant difference in pathological and behavioral changes and contributed to the accumulation of Iba1-positive cells. The arrangement of ambient temperature is useful for creating a rodent model with the appropriate severity of the targeted neuropsychological symptoms to establish a novel therapy for HIE.